2015
DOI: 10.1289/ehp.1408960
|View full text |Cite
|
Sign up to set email alerts
|

Insights into PBDE Uptake, Body Burden, and Elimination Gained from Australian Age–Concentration Trends Observed Shortly after Peak Exposure

Abstract: BackgroundPopulation pharmacokinetic models combined with multiple sets of age–concentration biomonitoring data facilitate back-calculation of chemical uptake rates from biomonitoring data.ObjectivesWe back-calculated uptake rates of PBDEs for the Australian population from multiple biomonitoring surveys (top-down) and compared them with uptake rates calculated from dietary intake estimates of PBDEs and PBDE concentrations in dust (bottom-up).MethodsUsing three sets of PBDE elimination half-lives, we applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
12
2
Order By: Relevance
“…This finding may be attributable to decreasing PBDE intake via breast milk combined with the effect of dilution of internal PBDE body burdens as the child grows. In contrast, a previous study conducted in Australia in 2006Australia in -2007 on pooled serum samples demonstrated that peak PBDE exposure occurs between the ages of two and three years, however, it must be noted that this study was conducted a decade prior to the current study, during which time serum PBDE concentrations from young Australian children have been rapidly declining (113,347).…”
Section: Concentrations In Faeces and Predicted Concentrations In Serumcontrasting
confidence: 58%
See 1 more Smart Citation
“…This finding may be attributable to decreasing PBDE intake via breast milk combined with the effect of dilution of internal PBDE body burdens as the child grows. In contrast, a previous study conducted in Australia in 2006Australia in -2007 on pooled serum samples demonstrated that peak PBDE exposure occurs between the ages of two and three years, however, it must be noted that this study was conducted a decade prior to the current study, during which time serum PBDE concentrations from young Australian children have been rapidly declining (113,347).…”
Section: Concentrations In Faeces and Predicted Concentrations In Serumcontrasting
confidence: 58%
“…Although the concentrations of some c-octaBDE and c-pentaBDE congeners in human serum and breast milk samples are decreasing, human exposure to PBDEs, particularly c-decaBDE, will continue to occur for decades to come, due to their continued presence in homes and the environment (345,346). Despite ubiquitous human exposure to PDBEs, there are still many data gaps about how exposure to these chemicals occurs, particularly for young children (347). While several studies elsewhere have assessed PBDE exposure pathways in children through a combined biomonitoring-survey approach to assess potential exposure pathways, the data internationally with regards to BDE-209 are limited, with no such data available in Australia (120,126,171,(348)(349)(350).…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes such studies confirm the elimination half-lives from earlier studies (Ritter et al 2009;Bu et al 2015;Wood et al, 2016b) while at other times they reveal inconsistencies in the data. Specifically, neither for North America (Ritter et al 2009;Wong et al 2013) nor for Australia (Gyalpo et al 2015) was it possible to reconcile contaminant intake estimates (accounting for both dietary and dust intakes), measured body burdens, and reported elimination half-lives for PBDEs. In both cases, the intake D r a f t estimates were judged to be too low, suggesting the existence of an unrecognized exposure pathway.…”
Section: Make Sense and Use Of Biomonitoring Datamentioning
confidence: 99%
“…Exposure assessments undertaken by modeling existing intake data underestimate the serum concentrations of these chemicals in children Gyalpo et al 2015). Estimates from applying models suggested there is a level of inconsistency between measured and modeled POP data in infants suggesting that intake in infants…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While pharmacokinetic modeling considering absorption, metabolism and excretion were not considered here, the reason for this disparity may be that food intake is not the dominant exposure route for infants and toddlers and rather placental transfer, breastfeeding and dust ingestion are important (Gyalpo et al 2015).…”
Section: Australian Comparisonsmentioning
confidence: 99%